PEMAKNAAN TOLERANSI BERAGAMA DI KOTA CILEGON - Ulumi, Helmy Faizi Bahrul; Kurniati, Erni; Bahriah, Nida; Rofahiyah, Fulajiatul; Wijaksana, Arif; Ahyadi, Yadi (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
Observing the diversity of perspectives on religious tolerance contributes significantly to fostering a more harmonious coexistence within societies characterized by varying religious affiliations. The overarching aim of this study is to investigate the viewpoints held by the populace of Cilegon regarding religious tolerance, focusing on partial comprehension, and to elucidate the community's perspectives on addressing the challenges associated with religious diversity within the city. Drawing upon findings from case studies and field data gathered through interviews with 16 participants representing the general populace, all adherents of Islam, and boasting diverse backgrounds spanning education and profession, this research delineates two primary dimensions of religious tolerance as perceived by the residents of Cilegon: acceptance and respect towards individuals holding divergent beliefs, ideologies, or faiths. Within the framework of tolerance, two delineated categories of boundaries emerge: theological and social. Both delineations uphold fundamental principles of acceptance and respect, with acceptance signifying acknowledgment of the existence of individuals adhering to different religious beliefs, while respect underscores the imperative for individuals to uphold principles of humaneness in their interactions with one another